Effect of oxytocin administered in the early stage of the oestrous cycle on the length of the oestrous cycle and levels of serum progesterone, plasma A vitamin and ?-carotene in cows - Yildiz, H; Çay, M (Scientific Technical Research Council Turkey, 2002)
The purpose of this study was to analyse the effect of the application of oxytocine in the early stage of the oestrous cycle on the levels of serum progesterone and plasma vitamin A and beta-carotene during the cycle. Five Swiss-Brown cows were used during two oestrous cycles. Blood samples were collected during the first cycle starting after synchronization and then a total daily dose of 100 I.U. oxytocine was applied subcutaneously as a half dose at 12 hour intervals on days on 4, 5 and 6 of the second cycle. During the same cycle, blood samples were again collected, from which serum and plasma were extracted. The levels of serum progesterone and plasma vitamin A and beta-carotene were determined from each sample and the correlations between these parameters were investigated. A statistically significant negative correlation was present between serum progesterone and plasma beta-carotene levels during the second cycle in cows (P<0.01). However, a mild negative correlation between these parameters in the first cycle and a mild positive correlation between serum progesterone and vitamin A levels in the second cycle were determined. Additionally, while during the second cycle the mean value of beta-carotene was found to be higher than during the first cycle (P<0.05), there was no statistically significant difference between mean values of serum progesterone and plasma vitamin A values during either oestrous cycle (P>0.05). It was concluded that the application of oxytocine during the early stage of the oestrous cycle has no effect on the length of the cycle, or serum progesterone, plasma vitamin A or beta-carotene levels.
Ineklerde siklusun erken döneminde uygulanan 0ksitosinin siklus süresi, serum progesteron, plazma vitamin A ve ?-karoten düzeyleri üzerine etkisi
Keywords: vitamin A; beta-carotene; progesterone; oxytocin; oestrous cycle; cows